Wireless sensor networks: creating smart infrastructure [Awarded the ICE 2010 Telford Gold Medal] - Hoult,N; Bennett,PJ; Stoianov,I; Fidler,P; Maksimovic,C; Middleton,C; Graham,N; Soga,K (Proceedings of the ICE - Civil Engineering, 2009)
The deterioration of civil infrastructure is a significant issue throughout the world. To manage infrastructure in a way that ensures safe and efficient operation, managers and engineers require data about its short- and long-term performance. This paper reports on the trial installations of wireless sensor networks in a suspension bridge, slab bridge, rail tunnel and water supply pipeline. Each installation is introduced in terms of hardware, measured parameters, sensors, sampling regimes and installationand operational challenges. Preliminary results from each system are discussed to illustrate the variety of information that can be made available to managers and engineers, and how this information canbe utilised and presented.